Driving Small and medium-sized enterprise Performance Through Product Innovation: The Roles of Strategic Orientation, Market Power, and Organizational Collaboration - Singgih Prabowo Almanda; Muhammad Riza Firdaus (Open Access Indonesia Journal of Social Sciences, 2024)
Small and medium-sized enterprises (SMEs) are essential contributors to economic growth and development. However, they often face significant challenges in maintaining competitiveness and achieving sustained growth, particularly in the current era of rapid technological advancements, globalization, and evolving market dynamics. This study aims to investigate the critical factors that drive product innovation and their subsequent impact on the performance of SMEs. A quantitative research approach was employed in this study. Data were collected through a survey administered to 69 Sasirangan Cloth SMEs in Banjarmasin, Indonesia. These SMEs are engaged in the traditional textile craft of Sasirangan cloth, which holds cultural significance in the region. Structural equation modeling (SEM) with partial least squares (PLS) was utilized to analyze the collected data. The findings of the data analysis reveal that strategic orientation, market power, and organizational collaboration have a positive and statistically significant impact on product innovation. This suggests that SMEs that adopt a market-oriented, entrepreneurial, and technology-oriented strategic approach, combined with efforts to develop market power and engage in collaborative relationships with other organizations, are more likely to foster product innovation. Furthermore, the study finds that product innovation plays a mediating role in the relationship between these factors and company performance, indicating that product innovation is a key mechanism through which strategic orientation, market power, and organizational collaboration contribute to enhancing SME performance. In conclusion, this study underscores the pivotal role of product innovation in driving SME performance. By developing and introducing new products or significantly improving existing ones, SMEs can differentiate themselves from competitors, attract new customers, and enhance their overall competitiveness.